IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI BIDANG STUDI PENDIDIKAN KEWARGANEGARAAN - Muhammad Yunan Suhardiyansyah; Budiono Budiono; Rohmad Widodo (University of Muhammadiyah Malang, 2016)
Research conducted at SMAN 9 Malang about, (1) Implementation of CharacterEducation by Study of Citizenship, (2) Describe the constraints faced, (3) Describe solution made in the implementation of Character Education by Study Of Citizenship. This research uses the nearing of qualitative research. Where researchers directly to collecting information related to the title of the study. The collection of data obtained from observation, interview, and documentation. As for the target of information are principal, waka kurikulum, waka student, teacher Citizenship Education, and the student of SMAN 9 Malang. Indicate thatthe results of research in Citizenship Education in SMAN 9 Malang loading about Character Education and devolep values’s character that exist in the state ideology that is Pancasila, strategic Citizenship Education teachers of SMAN 9 Malang are with model. Habituation or reinforcement. Evaluation is conducted by the Citizenship Education teacher at SMAN 9 are cognitive, affective and psychomotor student. Values in Citizenship Education also developed in school extracurriculier activities such as extracurricular activities paskibra in SMAN 9 Malang which also inserts character education such as discipline, responbility,independence, and nationalist. It’s just that in practice there are still constraints such as there are still a few of student who make mischief in school, many teacher and students who come school late. From the times or the impact that the school conducted globalisasi. The solution of the schools that model, an awareness of the self, the role of parents.